HIGH-TECH HUMAN-TOUCH FOR ONLINE COURSES: RULES AND PRINCIPLES FOR HUMANIZING YOUR ONLINE COURSE - Shnaikat, Khawla; AlQudah, Ayman Ahmed (European Scientific Journal, ESJ, 2015)
The noticeable progress and development in online learning and its technologies has made it necessary to pay attention on how to have high touch courses with high tech as well. Technologies sometimes make things complicated if it is not added intentionally. The aim of this study is to build a guide that explains how to make online courses more human. The answer to this question comes through a set of brilliant and sequenced steps that each instructor can follow to humanize online courses. This is presented after critically reviewing COI model, and accommodating the results of the COI with a real case study.